Analisis Beberapa Pemikiran Tajdid Muhammad Tahir Jalaluddin: An Analysis of Some of Tajdid Thoughts Muhammad Tahir Jalaluddin - Abdul Malik , Mohd Pua’ad; Abdul Hamid , Faisal @ Ahmad Faisal (Jurnal Usuluddin, 2021)
This article is a discussion the tajdid thinking of Tahir Jalaluddin. He is a famous reformist figure in Malaya at early 20th century. The pattern of his tajdid are very advanced and ahead of his time and relevant according to the contemporary context. By using document research instruments and content analysis, this study found that the concept of tajdid Tahir is clearly evident with a new feature fiqh pattern approach that includes and complies with the methods of Islamic law. The great impact of tajdid thinking pioneered by him has influenced the character of Islam in society as well as being a constant inspiration to current Malay Islamic scholars and reformers.